‘Say Cheese!': Humane halos from environmental practices in dairy production - Zamzow, Heidi; Basso, Frédéric (Frontiers in Sustainable Food Systems, 2022)
Awareness of the negative impacts of our food choices on planetary, human and animal health is growing. Research shows an increasing number of consumers consider ethical consequences when purchasing food. A new market sector has emerged which caters to the demands of these value-driven consumers. However, attempts to change the market through ethical purchases may be thwarted by advertising strategies which exploit the ‘halo effect', a cognitive bias which manifests when first impressions of one attribute influence subsequent evaluations of unknown attributes. This research investigates how two ethical domains, environmentalism and animal welfare, interact to influence consumer choice. In an online experiment, we recruited 267 participants and randomly assigned them to read either a pro-environmental, anti-environmental, or ethically neutral vignette about a cheese company. After being asked to rate the dairy on how well it treats its cows—an issue on which no information had been provided—participants indicated how frequently they would recommend the cheese compared to other brands. Results confirm that information about the company's environmental practices influenced perceptions of its animal welfare practices: a ‘humane halo' effect. Further, humane ratings predicted product consumption recommendations, indicating the humane halo acted as a mediator. Exploratory analyses suggest the strength of this mediated relationship depends on participants' environmental protection values, particularly if they received negative information. Our findings establish the existence of a cross-domain halo in food ethics and shed light on ways to increase the effectiveness of policies designed to shift consumers to more sustainable diets.